2018
DOI: 10.1177/0265407518779139
|View full text |Cite
|
Sign up to set email alerts
|

Transgender exclusion from the world of dating: Patterns of acceptance and rejection of hypothetical trans dating partners as a function of sexual and gender identity

Abstract: The current study sought to describe the demographic characteristics of individuals who are willing to consider a transgender individual as a potential dating partner. Participants (N = 958) from a larger study on relationship decision-making processes were asked to select all potential genders that they would consider dating if ever seeking a future romantic partner. The options provided included cisgender men, cisgender women, trans men, trans women, and genderqueer individuals. Across a sample of heterosexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 42 publications
0
38
0
1
Order By: Relevance
“…Randy's qualitative auto-ethnography illuminates his cultural experience as a trans-attracted, cisgender man. There is a dearth of literature that explores the experiences of those who partner with trans identified individuals, with the majority of existing research on gender transition (of the trans partner) or sexual interaction (Blair & Hoskin, 2019;Hsu, Rosenthal, Miller, & Bailey, 2016;Rosenthal, Hsu, & Bailey, 2017;Weinberg & Williams, 2010). Because of the emphasis on the trans partner or the sexuality of the relationship, the partner experience is often overlooked.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Randy's qualitative auto-ethnography illuminates his cultural experience as a trans-attracted, cisgender man. There is a dearth of literature that explores the experiences of those who partner with trans identified individuals, with the majority of existing research on gender transition (of the trans partner) or sexual interaction (Blair & Hoskin, 2019;Hsu, Rosenthal, Miller, & Bailey, 2016;Rosenthal, Hsu, & Bailey, 2017;Weinberg & Williams, 2010). Because of the emphasis on the trans partner or the sexuality of the relationship, the partner experience is often overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…Notaro (2018) asserts that the theory of trans-attracted men as repressed homosexuals is transphobic, acknowledging that this perspective imposes a binary system in which only cisgender men and women can provoke or feel arousal (p. 3). Cisgenderism or cissexism is another likely contributor to the fortitude of both the mythology and binary; the ideology that cisgender identities are normal delegi-timizes trans identities, expressions and experiences (Blair & Hoskin, 2019).…”
Section: Shamementioning
confidence: 99%
See 2 more Smart Citations
“…Despite these more positive findings for trans men, there is a recurring narrative that being open about transgender identity risks setting one up for a lonely life or at least one without romantic partnership. In their survey of nearly 1,000 (predominantly cisgender) respondents, Blair and Hoskin () found that 87.5 percent of participants excluded trans men and trans women as potential dating partners, with exclusion highest among heterosexual men and women, followed by gay men. Because of cisgender people's fixation on transgender people's anatomy and essentialist thinking that reduces trans people to their genitalia (Serano, ), scholars like Blair and Hoskin argue cisgender people's imagination in regards to trans bodies is a driving factor in why they fail to consider transgender people as romantic partners.…”
Section: In the Bubble: The Constraints On Trans Romance And Intimacymentioning
confidence: 99%